2019
DOI: 10.1056/nejmoa1908419
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor with or without Aspirin in High-Risk Patients after PCI

Abstract: BACKGROUND Monotherapy with a P2Y 12 inhibitor after a minimum period of dual antiplatelet therapy is an emerging approach to reduce the risk of bleeding after percutaneous coronary intervention (PCI). METHODS In a double-blind trial, we examined the effect of ticagrelor alone as compared with ticagrelor plus aspirin with regard to clinically relevant bleeding among patients who were at high risk for bleeding or an ischemic event and had undergone PCI. After 3 months of treatment with ticagrelor plus aspirin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
629
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 774 publications
(702 citation statements)
references
References 33 publications
(43 reference statements)
18
629
0
13
Order By: Relevance
“…As described in Figure 1 patients met our eligibility criteria. [11][12][13][14] Of these, 14 530 patients were randomized to monotherapy with a P2Y12 inhibitor, whereas 14 599 patients were randomized to standard dual antiplatelet therapy. Four trials tested P2Y12 inhibitor monotherapy after 1 to 3 month of DAPT vs P2Y12 inhibitor plus aspirin ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Figure 1 patients met our eligibility criteria. [11][12][13][14] Of these, 14 530 patients were randomized to monotherapy with a P2Y12 inhibitor, whereas 14 599 patients were randomized to standard dual antiplatelet therapy. Four trials tested P2Y12 inhibitor monotherapy after 1 to 3 month of DAPT vs P2Y12 inhibitor plus aspirin ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in the subgroup analysis of this study, there was no significant interaction between the type of P2Y12 inhibitors and the treatment effects of the two antiplatelet regimens on the bleeding events. The TWILIGHT study, enrolled patients undergoing PCI who are at high risk for ischemic or hemorrhagic complications, was associated with a 51% lower risk of bleeding. In contrast to these three studies, the results of The GLOBAL LEADERS trial showed that DAPT for 1 month followed by 23 months of ticagrelor alone did not reduce the incidence of bleeding than the traditional DAPT treatment regimen .…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that the switched DAPT strategy was superior in terms of bleeding regardless of the initial platelet reactivity [73]. The recent TWILIGHT study further supported a strategy based on a shorter DAPT [74]. This study randomized more than 7000 high-risk patients who had undergone an uneventful 3-month course of DAPT after PCI using ticagrelor, to either continue with DAPT for an additional 9 months or stop aspirin.…”
Section: Do Platelet Function Tests Help To Avoid Bleeding Events?mentioning
confidence: 98%
“…In these circumstances, the benefit of sustained DAPT may translate into a smaller absolute ischemic event risk reduction, which might be potentially outweighed by the associated higher risk of bleeding [6]. Since aspirin yields limited additional platelet inhibition when associated with P2Y 12 inhibitors, aspirin-free strategies have been evaluated in several recent randomized controlled trials enrolling ACS or PCI patients; in some of these studies patients also had an indication for chronic oral anticoagulation (OAC) [7][8][9][10][11][12][13][14][15][16][17][18][19]. Most of these trials (but not all) reported lower rates of bleeding without aspirin, but all of them were underpowered as to properly evaluate the associated ischemic risk.…”
Section: Introductionmentioning
confidence: 99%